Monitoring Salmonella sp dan Escherichia coli dalam Bahan Pakan Ternak (Salmonella sp and Escherichia coli Monitoring in the Animal Feed Ingredients) - Widodo Suwito (Buletin Peternakan, 2010)
Quality of livestock feed affects production and animal health. Fish and bone meal is animal feed ingredients that need to be monitored because highly contaminated with of Salmonella sp and E. coli. Salmonella sp and E. coli arepathogen causing diarrhea in cattle and humans. The aim of this study was to investigate both E. coli and Salmonella contamination animal feed ingredients. A total of 38 animal feed ingredients samples from a poultry farm in Sukabumiconsisting of 15 samples fish meal, bone meal 13 samples and corn 10 samples. These samples were analyzed for Salmonella sp and E. coli by isolation and identification using biochemical analysis. Salmonella Weltevreden wasisolated from fish meal at rates of 6% from the 15 samples. E. coli was isolated at rates of 6% from the 15 fish meal samples and 7% from 13 bone meal samples, while corn samples were free from Salmonella sp and E. coli. This studyshowed that bone meal and fish meal was contaminated slightly by Salmonella Weltevreden and E. coli.(Key words: Feed, Livestock, Salmonella sp, E. coli)